PENGARUH METODE PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS SD NEGERI 1 PAMPANGAN - Zeta Ulpatara Wandira; Kiki Aryaningrum; Mega Kusuma Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research was conducted at SD Negeri 1 Pampangan with the purpose of this study was to determine the extent of the influence of the application of differentiated learning methods on improving student learning outcomes in Natural and Social Sciences (IPAS) subjects. In this study there are two variables, namely variable x differentiated learning method and variable y learning outcomes. The method used in this research is quantitative research method with experimental type and quasi-experimental design, this research design uses nonequivalent control group design. The sample in this study was class IV totaling 15 students for the experimental class and 16 students for the control class. The instrument validation techniques in this study include validity tests, reliability tests, difficulty levels, and differentiating power. In this study using two test stages, namely, the initial test and the final test, using two classes, namely, experimental and control classes. After analysis, before the application of differentiated learning methods in the experimental class, the average student score was 72.00. After the learning was done, the average increased to 90.67. In the control class, the pretest average value of 63.13 increased to 68.75 in the posttest. Based on the results of statistical analysis using the Independent Samples t-Test test in the t-test for Equality of Means section, a significance value (Sig. 2-tailed) of 0.000 was obtained. This value is smaller than the specified significance level of 0.05, so it can be concluded that there is a statistically significant difference between student learning outcomes in the experimental and control classes. It can be concluded that there is an effect of differentiated learning methods on the learning outcomes of grade IV students in the IPAS subject of SD Negeri 1 Pampangan